THE SACREDNESS OF THE SEBLANG RITUAL OLEHSARI AND ITS EXISTENCE AS THE DOMINANT CULTURE - Nawang Sukma Ayuningtyas; Yhesika Pramudiani; Asydiqul Fanju (Jurnal Scientia, 2023)
The existence of the Seblang ritual is still one of the cultural icons of Banyuwangi. Seblang is an authentic ritual because it is only found in the villages of Olehsari and Bakungan. Even though they sound the same, the two have different ritual processes. This study discusses the sacredness of the Seblang bysari ritual and its existence as the dominant culture, with the aim of describing the forms of the sacredness of the Seblang bysari ritual within the frame of Raymond Williams' dominant cultural perspective. The Seblang ritual as the dominant culture has an irreplaceable position because of the form of representation of the original culture itself. Departing from that, then the creation of the Seblang dance was born as a form of residual culture or an alternative to the Seblang ritual. Meanwhile, in the dynamics of its development, the Seblang ritual experiences acculturation between culture and religion, or is referred to as an emergent. The method used in this research is descriptive qualitative method with an ethnographic study approach. This study uses data mining techniques through observation and interviews from sources related to the sacredness of the Seblang bysari ritual. This research describes the existence that has survived to this day in the Seblang ritual, which in the end the Seblang ritual became a culture that was conserved in the form of a dance created by Seblang through the intervention of the Culture and Tourism Office of Banyuwangi Regency. The theory in analyzing this research is Raymond Williams' theory of culture.